2006
DOI: 10.1143/jjap.45.3165
|View full text |Cite
|
Sign up to set email alerts
|

Application of HfSiON to Deep-Trench Capacitors of Sub-45-nm-Node Embedded Dynamic Random-Access Memory

Abstract: In this study, the potential of HfSiON as the node dielectric of deep-trench (DT) capacitors was investigated for the first time. It was found out that a uniform thickness and a uniform depth profile of each component in DT can be obtained by the ALD process which utilizes the catalytic effect of the Hf precursor and Si precursor. In addition, the mechanism underlying leakage current was analyzed and it was revealed that residual carbons in the film contribute to the Poole–Frenkel current through the film. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Obviously the type and amount of impurities also will be different for these precursors and differences in film density, film composition, roughness, crystallinity can result in different performance of the films in semiconductor devices. The chlorine incorporated in gate stack from HfCl 4 is thought to be a fairly acceptable trace impurity (22), possibly more than carbon from metal amide (23). In one study, both types of precursors yielded HfO 2 transistors with comparable electrical characteristics ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously the type and amount of impurities also will be different for these precursors and differences in film density, film composition, roughness, crystallinity can result in different performance of the films in semiconductor devices. The chlorine incorporated in gate stack from HfCl 4 is thought to be a fairly acceptable trace impurity (22), possibly more than carbon from metal amide (23). In one study, both types of precursors yielded HfO 2 transistors with comparable electrical characteristics ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that a factor which may be contributing to the leakage differences across the wafer is differences in in-film carbon due to the ligands in the metallorganic precursor. It has been previously shown that a strong correlation exists between in-film carbon and leakage current using metallorganic precursors and an ozone oxidant in an ALD process for the deposition of an HfO 2 -based dielectric(13). Further work would be required to improve the across wafer non-uniformity for the O 3 -based process possibly by optimizing pulse and purge times for growth on the bottom electrode.Fig.…”
mentioning
confidence: 99%
“…It offers high quality, pinhole-free, and conformal thin films with precise thickness control down to subnanometers . During the past decades, it has demonstrated significant advancements in growing gate dielectrics in complementary metal oxide semiconductor (CMOS) devices, insulating layers in memory devices, optical coating in photonic devices, and surface modification/functionalization for catalysts. Many research efforts have been devoted to explore the roughness control, surface chemical properties, and conformal coating features of ALD films, which are either amorphous or crystalline. ,, Contemporary research on ALD extends to exploring continuous and rapid film growth at ambient pressure and conformally depositing quantum dots, nanowires (NWs), or epitaxial films. Such novel advances would make ALD a powerful and versatile nanomanufacturing tool beyond a thin film coating technique. Nevertheless, current understanding of ALD growth is mainly based on surface chemistry, that is, molecular level chemical reactions .…”
mentioning
confidence: 99%